Cortical spreading depression dynamics can be studied using intrinsic optical signal imaging in gyrencephalic animal cortex - Santos, Edgar; Schöll, Michael; Sánchez-Porras, Renán; Kentar, Modar; Orakcioglu, Berk; Unterberg, Andreas; Dickhaus, Hartmut; Sakowitz, Oliver (Brain Edema XV, 2013)
Objective: The aim of this study was to co-record electrical changes using electrocorticography (ECoG) and blood volume changes using intrinsic optical signal (IOS) imaging during the induction, propagation, and termination of cortical spreading depolarizations (CSDs). Methods: Anesthetized male swine were craniotomized and monitored over 16-20 h. A ten-contact electrode strip was placed on the cortex of one hemisphere for ECoG. An optical imaging recording was implemented using a camera with an optical bandpass filter (564 nm, FWHM:15 nm) and a full spectrum light source. CSDs were induced by mechanical and KCl stimulation. Co-occurrences of ECoG baseline shifts and blood volume changes around electrodes were identified. Results: A mean of 3 CSDs per hour were induced, in a total of 4 swine during 80 h of recording. The propagation of the CSDs increased progressively over the monitoring time. IOS enabled us to clearly visualize the induction, propagation, and termination of CSDs with a spatial resolution within the sub-millimeter range. Every CSD recorded using ECoG could also be observed in IOS imaging, although some blood volume changes of CSDs were observed that terminated before reaching any of the ECoG electrodes. Conclusion: IOS imaging enables an in vivo evaluation of CSD dynamics over a large surface of gyrencephalic brain.
Gesehen am 17.02.2022